CAMKK2, Regulated by Promoter Methylation, is a Prognostic Marker in Diffuse Gliomas. (25th March 2016) - Liu, Da‐Ming; Wang, Hong‐Jun; Han, Bo; Meng, Xiang‐Qi; Chen, Ming‐Hui; Yang, Dong‐Bo; Sun, Ying; Li, Yong‐Li; Jiang, Chuan‐Lu
Summary: Aims: To explore the expression, methylation pattern, the prognostic value, and the biological consequences of CAMKK2 in gliomas. Methods: The expression and methylation pattern of CAMKK2 was inferred and validated from mRNA expression profile (N = 866) and methylation profile (N = 426) of glioma tissue samples, and independent samples were used for further validation by IHC and pyrosequencing. To explore the function of CAMKK2 in gliomas, in vitro studies, colony formation assays and migration and invasion assays were performed. Results: We found the upregulation of CAMKK2 in high‐grade glioma samples was associated with promoter hypomethylation. An elevated expression of CAMKK2 was associated with worse prognosis. By in vitro assays, we demonstrated that CAMKK2 could promote cell migration, invasion, and proliferation. Conclusions: The expression level of CAMKK2 could be regulated by promoter methylation. CAMKK2 serves as a prognostic marker in gliomas and could be a potential therapeutic target in gliomas.